Manifestation of existential issues as a brilliant function for quality of matrimony - Kalantarkousheh, Seyed Mohammad; Hassan, Siti Aishah; Abdul Kadir, Rusnani; Abu Talib, Mansor (Marsland Press, 2011)
There are some important issues in marital counselling which are discoursed in Existential thought. These issues are freedom, time, human communication, meaning of life, and anxiety, which are shared by the existential counsellors and philosophers. Even though there are full potentials of the existential issues to be applied during counselling sessions, most of them are ignored by couple counsellors. The purpose of this article is to highlight these issues as the key concepts in four different counselling theories of Existential thought. We found that, each theory used only certain issues as the key concepts. Therefore, this study gathers all of the applied existential issues for a future comprehensive marital counselling model. Applying these issues together seems to be a brilliant function for quality of matrimony.